2020
DOI: 10.7196/samj.2020.v110i2.13969
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 polymorphisms and their effects on tacrolimus exposure in an ethnically diverse South African renal transplant population

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…In this regard, Cheung et al studied a population of 86 adult Chinese kidney transplant patients and found that CYP3A5 expressers needed a higher TAC dose compared with the nonexpressers [ 25 ]. Similar results were shown in several other studies conducted in different ethnic groups and post-transplant time periods [ 26 , 27 , 28 , 29 , 30 ] and by Muller et al, who also found that CYP3A5*3/*3 carriers showed higher inter-patient variability than CYP3A5*1/*1 and *1/*3 carriers [ 31 ]. Similarly, Gervasini et colleagues observed that CYP3A5 expressers required a higher TAC dose than nonexpressers, also showing a lower pre-dose concentration [ 32 ].…”
Section: Resultssupporting
confidence: 89%
“…In this regard, Cheung et al studied a population of 86 adult Chinese kidney transplant patients and found that CYP3A5 expressers needed a higher TAC dose compared with the nonexpressers [ 25 ]. Similar results were shown in several other studies conducted in different ethnic groups and post-transplant time periods [ 26 , 27 , 28 , 29 , 30 ] and by Muller et al, who also found that CYP3A5*3/*3 carriers showed higher inter-patient variability than CYP3A5*1/*1 and *1/*3 carriers [ 31 ]. Similarly, Gervasini et colleagues observed that CYP3A5 expressers required a higher TAC dose than nonexpressers, also showing a lower pre-dose concentration [ 32 ].…”
Section: Resultssupporting
confidence: 89%
“…In agreement with our findings, it has been observed that CYP3A5 expression is not associated with IPV of clearance, absolute concentration, or predicted area under the concentration-time curve (AUC) of tacrolimus among stable adult KTRs in previous studies [ 10 , 25 , 26 , 27 , 28 ]. In two studies by Pashaee et al [ 25 ] and Spierings et al [ 26 ], the proportions of KTRs with IPV of relative clearances of tacrolimus lower than the median values observed were comparable between CYP3A5 expressers and nonexpressers.…”
Section: Discussionsupporting
confidence: 93%
“…Given the fact that CYP3A5 expressers require a dose of tacrolimus approximately twice as high as CYP3A5 nonexpressers to achieve the same tacrolimus levels, it has been hypothesized that CYP3A5 expressers could be more susceptible to higher IPV [ 32 ]. On the other hand, it has also been postulated that since tacrolimus metabolism in CYP3A5 nonexpressers relies predominantly on the activity of CYP3A4 which is much more prone to induction and inhibition [ 33 ], CYP3A5 nonexpressers might be more susceptible to higher IPV [ 28 ]. The results of the present study do not support these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In view of the high prevalence of CYP3A5 expression in South African transplant recipients, high tacrolimus dose requirements are often necessary and result in substantially increased immunosuppression costs. 16 Nevertheless, in view of patient safety concerns, the continued mandatory use of PIs was reconsidered in 2014. 12 TDF has been well described to be associated with tubular nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%